Nursing Students’ views on Code of Ethics, Commitment to the Ethic of, Academic Dishonesty and Neutralization behaviors - Nasrin Mokhtari Lakeh; Mehran Nafar; Atefe Ghanbari Khanghah; Ehsan Kazemnezhad Leili (Journal of Holistic Nursing and Midwifery)
Introduction: Commitment to the ethics of caring in nursing profession is the center of nursing values and it necessitates honesty as its fundamental element. Nursing students dishonesty in classroom and clinical situations has the potential to jeopardize nursing practice. Academic misconduct contributes to inaccurate evaluations of nursing students knowledge level. Neutralization behaviors are techniques that protect the individual from self-blame. Some faculties use nursing code of ethics to prevent academic dishonesty. Objective: This study aims to determine nursing student s views on academic dishonesty, neutralization behaviors, code of ethics and commitment to the ethics of caring in nursing students of Guilan University of Medical Sciences in 2012. Methods: In this cross-sectional study, 193 nursing students of Guilan University of Medical Sciences were chosen by census method and data were collected by a three part questionnaire. Data were analyzed using Pearson Correlation, Independent t-test and back ward regression test to determine the relation between dependent and independent variables and effective predictors of commitment to ethics of caring in nursing students. Results: Findings of this study revealed that most study respondents were unaware of nursing codes of ethics (79.8%). The results indicated that women have more positive attitude toward nursing code of ethics (p= 0.002) and commitment to ethics of caring (p=0.004) but they have more negative attitude toward neutralization behavior (p=0.001) and academic dishonesty (p=0.007). Multiple regression test showed that attitude toward nursing code of ethic made the strongest unique contribu-tion to predicting a commitment to ethic of caring within the nursing profession (β=0.666, p=0.0001). Conclusion: Attitude toward nursing codes of ethics is the strongest predictor for commitment to ethic of caring therefore teaching students these codes can have an important role in providing ethical care to patients.